(untitled) (Bioscience Journal, 2023)
The objective of this study was to evaluate whether individuals with chronic renal failure (CRF) undergoing hemodialysis treatment have more salivary and oral mucosa alterations when compared to healthy individuals, through a systematic review followed by meta-analysis. A systematic literature review was performed, evaluating randomized clinical trials found in the Proquest, Embase, Scopus, Cochrane Library, Web of Science, Lilacs and Pubmed databases, using MeSH terms and other keywords. Initially, 40 articles were included in the study and, after reading the complete articles, only 15 clinical trials that analyzed oral lesions and salivary changes in patients with CRF undergoing hemodialysis treatment were eligible. Most of the clinical studies included were cross-sectional and composed of a study group and a control group. The mean age of participants in the study group was 50.19 years and in the control group, 48.95 years. The most common oral alterations found in the CRF group in relation to the control group were xerostomia, uremic breath, dysgeusia, coated tongue, gingival bleeding and pale mucosa. The salivary flow of patients with CRF was 46.6% lower than the control group. The salivary pH in the study group was also more alkaline when compared to the control group. Greater amounts of urea, phosphate, C-reactive protein and total proteins were found in the saliva of individuals with CRF. Individuals with CRF undergoing hemodialysis are more prone to changes in both the quantity and quality of saliva, as well as having a greater amount of oral changes.